Турция и СССР (Россия): Некоторые проблемы взаимоотношений после Второй мировой войны - Корхмазян, Рипсиме («Զանգակ - 97»)
The paper deals with the development öf relations between Turkey and the USSR afiter 1945,'the eharacter of which during the final phase of the war had grown up into severe confrontation. The attempt of Turkey to aid Germany, its anti-Soviet, anti-Communist and anti-Slavic policy lead to the denonciation of the 1925 treaty of friendship and neutrality by the USSR. As a response to Turkish government to sign a treaty, the USSR demanded to revise the regime of the Black Sea, to permit to found there Soviet military base, and return territories of Armenia and Georgia seized by Turkey in 1921. The Soviet government had put this demands on Berlin (Potsdam) conference.
Keywords: История; Политика